The Precariousness On Apps’ Delivery Drivers Work Conditions - Labruna, Felipe (2021)
This scientific article intends to deepen the discussions about the phenomenon of the transformation of labor relations through digital platforms (“applications” or “apps”) and the consequent precariousness of work conditions and degradation of the social rights of delivery drivers, bringing new elements in order to propose a concise regulatory environment that takes on the new difficulties brought by those technologies. This technological change concerns an innovative worldwide trend of administration, management and dominance of labor relations in virtual environments, causing a harmful effect to the delivery worker known as the “uberization” of his workforce. That said, this paper aims to do a brief legislative research on Labor Law’s history of concession and regulation in Brazil and to analyze, by using a theoretical approach, how the work through the mentioned digital platforms/applications demands a greater state regulation of its practice and use.